ANALISIS PRODUKTIVITAS TENAGA KERJA PADA PEKERJAAN PASANGAN BATA PERUMAHAN TIPE 36 (Studi Kasus pada Perumahan Griya Putri Tanjung Kota Bengkulu) - Yulianty, Chindy; Supriani, Fepy; Gunawan, Agustin (Inersia: Jurnal Teknik Sipil, 2021)
The process of housing development is inseparable from labor productivity. This study aimed to determine the value of LUR (Labor Utilization Rate), workgroup productivity, and dominant factors that influence the masonry work in Griya Putri Tanjung Housing. The method used in the research was field observations for six houses by observing the effective work time, contribution work time, and ineffective work time, calculating the area of bricklaying and questionnaires to 12 workers. The questionnaires were processed with SPSS 24. The results obtained showed that the highest worker utility factor (LUR) was on day 2 of 88.89%. The Average LUR in Putri Tanjung Griya Housing is greater than 50%, so the work utility factor reaches the effective time. The highest average productivity of each workforce is on the 3rd day by a productivity value of 1.51 m2/hour/person. The most dominant factor was the time factor and implementation conditions (up to 82%), then the physical factor of labor (32,8%), managerial (-24,1%), the background of the employee (19,1%). The lowest factor was the group factor and the expertise of the workforce by a percentage of influence of         -17,5%. Keywords: housing, labor, bricklaying.